Dehydroepiandrosterone plus climen supplementation shows better effects than dehydroepiandrosterone alone on infertility patients with diminished ovarian reserve of low-FSH level undergoing in-vitro fertilization cycles: a randomized controlled trial. Issue 1 (December 2016) - Zhang, Huanhuan; Chu, Yaping; Zhou, Ping; He, Xiaojin; Xu, Qianhua; Zhang, Zhiguo; Cao, Yunxia; Wei, Zhaolian
Abstract Background This study aimed to assess the effect of dehydroepiandrosterone (DHEA) plus climen (estradiol valerate and cyproterone acetate drug combination) on infertility patients with diminished ovarian reserve (DOR) and to determine if the combination of DHEA plus climen is superior to DHEA alone in improving ovarian response. Methods A total of 124 women were randomized into the DHEA group (n  = 64) and the DHEA plus climen group (n  = 60) for 12 weeks before being subjected to in-vitro fertilization (IVF) cycles. To investigate if there is a FSH-related difference on the effect of the addition of climen, the DHEA group and the DHEA plus climen group were further divided into four subgroups according to a basal FSH level cut-off of 10 mIU/ml. We performed a comparison of Day 3 blood samples before and after treatment and IVF outcome parameters, including AMH, FSH, E2, AFC, oocytes retrieved, MII oocyte numbers, embryo numbers and accumulated embryo scores. Results After 12 weeks of pretreatment, the DHEA plus climen group demonstrated a significantly higher level of AMH (P  = 0.001) and a significantly lower level of FSH (P  = 0.001) compared with the DHEA group. When the two groups were divided into four subgroups based on the FSH cut-off of 10 mIU/mL, a significant increase of AMH (P  = 0.034) was found in the high-FSH DHEA plus climen group, whereas there was no significant difference in the high-FSH DHEA group (P  = 0.322). A significantly higher accumulated score of embryos was observed in the low-FSH DHEA plus climen group compared with the low-FSH DHEA group (P  = 0.034). Conclusions These observations suggest that patients with DOR of a low-FSH level might benefit more from DHEA plus climen supplementation than from DHEA supplementation alone.